Speech communication conceptual art and reflection on the products of art education students (Journal of the College of Basic Education, 2022)
The aim of the present research is to: 1- Know the communicative discourse of conceptual art in postmodern art. 2- The mechanisms of conceptual art work are defined in the products of art education students. The analytical method was used, and the research community formed the artistic productions accomplished by the students of art education for the 2015-2016 academic year, which amounted to (53) artistic products, of which the researcher chose (3) models represented by embodying the body art - the art of language - the art of performance. In a random way to represent the research sample, and to verify the research goal, the researcher built an analysis tool that included (5) axes presented to a group of experts to verify the validity factor of the form. As for the most important conclusions reached by the researcher are:1-The artistic productions accomplished by the students of art education are based on various structures, including in their communication discourse of conceptual art, so that it dealt with the art of the body - the art of language - the art of performance, which formed a basic reference for the symbols in those products.2-Symbols and figures were associated in artistic productions to be artistic expressions that formed a distinct conceptual discourse of a symbolic aesthetic verb away from the usage verb that sometimes represents a functional verb that is transformed into an artistic concept to work within the communicative discourse of conceptual art